Education Quality Management Model at Integrated Islamic High Schools in Banten Province - Asep Muljawan; Suhendar Sulaeman; Saiful Bahri (Asian Social Work Journal, 2023)
Education quality management has an important role in improving and developing school quality. The purpose of the research is to analyze and find a model of education quality management in Integrated Islamic High Schools. This research approach uses analytical descriptive qualitative. The results of this study show; (1) The concept of education quality management in the three schools has been owned and implemented through the leadership of the principal effectively, this is shown by paying attention to input, process, output, and outcome. In the input component, the school focuses on the quality of incoming personnel, in the process component, the school conducts Deming's PDCA then Juran's Pareto principle. In the output and outcome, pay attention to Crosby's zero defect. And all of them are framed with the spirit of Islam, Alqur'an, and Hadith (Religious). (2) The school pays attention to and carries out factors in realizing quality schools; leadership, attachment and involvement of school components, efforts to improve the professionalism and welfare of teachers, integration of the 2013 curriculum (8 SNP) with the unique curriculum of Integrated Islamic High School, optimization of infrastructure including information technology and financing and partnerships. (3) The impact of education quality management in the three schools has implications for strengthening two aspects, namely strengthening the quality of graduates and strengthening institutions and human resources. Based on the results of the substantive findings, the formal findings in this study are a model of education quality management based on system thinking leadership.